THE EFFECTIVENESS OF LAW NUMBER 6 OF 2014 CONCERNING VILLAGE IN RELATIONSHIP WITH COMMUNITY PARTICIPATION - Nelwan Nelwan (Fox Justi : Jurnal Ilmu Hukum, 2021)
This study aims to determine how the application and the extent to which the factors that influence Law Number 6 of 2014 concerning Villages are related to the participation of the people of Bojo Village, Budong-budong District, Central Mamuju Regency. The research method used is "Field Research and Study literature”, the sources were obtained from interviews and various literatures related to the effectiveness of Law Number 6 of 2014 concerning Villages qualitatively and presented descriptively. The results of this study are as follows (1) In the application of Law Number 6 of 2014 concerning Villages it can be said that it is not effective in the community of Bojo Village, Budong-budong District, Central Mamuju Regency. During the enactment of the Village Law, there were still many residents who did not know the existence and contents of the Village Law, and there was still very little community participation in various activities carried out in Bojo Village. (2) In its implementation, the Village Law Number 6 of 2016 has several factors that affect the effectiveness of its enforcement, one of which is that the condition of the community is mostly farmers and plantation workers causing frequent Village activities that are not followed by the community on the grounds that they are more concerned with doing work in order to fulfill their needs. necessities of life